IMPLEMENTASI MANAJEMEN STRATEGIS PROGRAM FULL DAY SCHOOL (FDS) DI MADRASAH IBTIDAIYAH AMANAH DESA TANGGUNG KECAMATAN TUREN KABUPATEN MALANG - Hisbullah Huda (Damhil Education Journal, 2022)
This study aims to determine the Implementation of Strategic Management Full Day School Program at MI Amanah Responsibilities, Malang Regency. This study uses a descriptive qualitative approach. Data was collected using observation, interview and documentation techniques. Data analysis was carried out in a qualitative descriptive way with an interactive model. The analysis process is carried out from the time the data is obtained until the completion of the report writing. The results obtained from the implementation of strategic management of the full day school program at MI Amanah Tanggung, Malang Regency contain two things, namely academic and non-academic achievements and their details. In addition, it details the various academic and non-academic achievements that have been achieved by madrasas over the past three years, USBN's achievements have increased sharply, and many graduate students who continue to favorite junior high schools. The supporting factors for the full day school program at MI Amanah Tanggung, Malang Regency can be detected as 23 points, including special treatment from the management for full day school classes, and good and well-maintained facilities, the presence of accompanying teachers who are always ready to help and others. The inhibiting factors for the Full Day School Program can be found to be 22 points, among others, there are still some students whose academic achievements are below the curriculum target, there are still doubts that are heard from some people about the full day school program.Keywords: Management, Strategy, Program, Full Day School